EXTRACTION OF NON-TRADITIONAL TYPES OF HYDROCARBON RESOURCES BY APPLICATION OF ELECTROMAGNETIC ENERGY - Makogon Yu.F.; Sayakhov F.L.; Khabibullin I.L. (My University, 1989)
Recently, there is a significant interest in prospecting for and developing non-traditional types of hydrocarbon resources, as petroleum bitumens, gas hydrates, oil shales, and ozokerite. Significant reserves of such resources exist, and they constitute an energy and raw-materials alternative to oil and gas. Also, natural bitumens contain significant quantities of valuable minerals and compounds. Under formation conditions, these alternative hydrocarbon-containing substances completely fill the pore space and exist in solid, crystalline or amorphous state. Their extraction by familiar oil-and-gas production techniques is therefore impossible. There is a need for new techniques of hydrocarbons extraction by open-pit mining and in wells. One such method involves the application of electromagnetic energy, which is injected into the formation in the form of high-frequency electromagnetic waves. The interaction of electromagnetic waves with the rocks generates heat sources and ponderommotive forces and physicochemical surface phenomena, electrocapillary and electrosurface effects which could be useful in their production.